Fairtrade UK in Retrospect: From the Niche Genesis to the Revelatory Mainstreaming Marketing Strategy Era (Late 1950s - Late 2000s) - Yamoah, Fred A. (International Review of Management and Marketing, 2019)
This paper critically and systematically examines the discourse surrounding the history of fairtrade development, stakeholder involvement and the implications of mainstreaming marketing strategy on consumer engagement in the UK from the late 1950s to the early 2010s. It highlights the pioneering role of Oxfam and Traidcraft in the late 1950s; presents a novel structure of the fairtrade industry and highlights the UK fairtrade industry's market leadership and the benefits of mainstreaming. It also espouses the implications of mainstreaming strategy on consumer engagement and the long-term marketing viability of the industry in the UK. Keywords: Fairtrade UK industry; mainstreaming; consumer engagement JEL Classifications: M30, M31, Q01 DOI: https://doi.org/10.32479/irmm.8288